2018
DOI: 10.1007/s12445-017-1014-7
|View full text |Cite
|
Sign up to set email alerts
|

Orgaandonatie na euthanasie

Abstract: Sinds 2012 kunnen in Nederland organen en weefsels na eu thanasie gedoneerd worden. Huisartsen doen het leeuwen deel van de euthanasiemeldingen; zij zijn ook bij uitstek in de positie om potentiële orgaandonoren te identificeren. Dat stelt hen geregeld voor de keuze of zij dit ingewikkel de traject, waarvan de uitkomst onzeker is, willen ingaan. Euthanasie en orgaandonatie blijven strikt gescheiden pro cedures en een euthanasiewens mag nooit voortkomen uit de wens een orgaan te doneren. Slechts 10% van de euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Whereas it is very small in SnS‐SnS 2 , it is significant in LaS‐TaS 2 transferring electronic charge from the LaS to the TaS 2 layers. Both structures have been synthesized experimentally, at least in related forms such as e. g. scrolls ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas it is very small in SnS‐SnS 2 , it is significant in LaS‐TaS 2 transferring electronic charge from the LaS to the TaS 2 layers. Both structures have been synthesized experimentally, at least in related forms such as e. g. scrolls ,…”
Section: Resultsmentioning
confidence: 99%
“…It occurs as 2D layered material only in combination with other layers, e.g. niobium sulfide, or tantalum sulfide ,,. To date, only a few studies have been published concerning the combination of SnS and SnS 2 layers or tubes,, and the combination of LaS and TaS 2 layers ,.…”
Section: Introductionmentioning
confidence: 99%
“…Patients requesting MAiD who want to donate their organs are usually hospitalized in order to proceed with this process. 3,21,22,27,31,41,43,45,46,48,49,53,54,58,61,70,73,76,[78][79][80]96 This is due to many reasons, including having more control over the patient's underlying health condition, 3,27,46 timely transfer to the operating room to reduce warm ischemia time (WIT), 21,27,31,41,46,61,73 and easy access to health care services and resources. 27,46,73 Eight reports 21,27,41,43,46,54,73,78 provided detailed descriptions of the clinical pathways involved in organ donation in the hospital.…”
Section: Clinical Pathways For Organ Donation Following Maidmentioning
confidence: 99%
“…For all settings, organ donation following MAiD involves the allocation of resources and logistical challenges, 6,17,24,29,34,37,41,46,48,49,63,65,69,72,75,81,82 including the timing of the procedure, 65,75 mechanism of death, 65,75 availability of health care professionals for the procedure, 24,29,41,46,63 higher costs, 24,72 additional testing, 46,75,82 and administrative issues 34 (eg, only physicians or nurse practitioners with hospital privileges can be involved in the procedures). Also, some authors reported that MAiD, medical assistance in dying; OD, organ donation *Varies between countries; in some places the patient must start the conversation around OD; in others the health care professional may start this conversation.…”
Section: Clinical Pathways For Organ Donation Following Maidmentioning
confidence: 99%
“…These structures can be described by superspace (higher than three dimensions). For this paper, we are using a variation of the crystallographic notation that can easily be extended into higher dimensions ( van Smaalen, 2005van Smaalen, , 2007. Superspace modulations are identified by the number of extra dimensions needed to describe the diffraction pattern: (3+d)D, where d is the number of extra dimensions.…”
Section: Superspace Notationmentioning
confidence: 99%